Improving Elementary School Students' Learning Outcomes using the Problem Based Learning Model - Deni Komarudin (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Education plays a critical role in shaping students' intellectual and personal growth, and the effectiveness of teaching methods is essential for improving student outcomes. Objective: This study aimed to investigate the use of the Problem-Based Learning (PBL) model to enhance the learning outcomes of elementary school students in Islamic Religious Education (Pendidikan Agama Islam) at SD Negeri 01 V Koto, Kab. Mukomuko. Method: The research employed a Classroom Action Research (CAR) design, which included cycles of planning, action, observation, and reflection. Data were collected through pre-cycle assessments, followed by evaluations after the first and second cycles. Result: The results demonstrated a significant improvement in student learning outcomes, with the percentage of students meeting the Minimum Completion Criteria (KKM) increasing from 30% in the pre-cycle to 95% in the second cycle. The findings highlight that the implementation of PBL effectively encouraged active student participation, promoted critical thinking, and enhanced problem-solving skills. Conclusion: The study concluded that the Problem-Based Learning model significantly improved the learning outcomes of elementary school students in Islamic Religious Education, promoting both cognitive and affective development. Contribution: This research contributes to the understanding of how PBL can be applied in elementary education to boost student engagement and achievement, offering valuable insights for teachers and educational policymakers aiming to improve educational practices.